The Role of Visum Et Repertum in Exposing Criminal Acts of Persecution (Study of Decision Number 330/Pid.B/2023/PN. Cbi) - Prawitasari, Nining Yurista; Sayudi, Akbar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this study is to determine the important role of Visum Et Repertum in proving criminal acts of persecution.  This research uses normative juridical legal methods, namely legal research conducted by examining textbooks of legal experts, legal journals, and scientific works of legal experts and primary data including legislation and judges' decisions. The results showed that the role of visum repertum in Decision Number: 330/Pid.B/2023/PN. CBI, is very important as one of the evidence in the trial in accordance with article 184 paragraph (1) of the Code of Criminal Procedure, and is subject to the consideration of the Judge.